2002
DOI: 10.1128/iai.70.9.5065-5074.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cruzipain Induces Both Mucosal and Systemic Protection againstTrypanosoma cruziin Mice

Abstract: Cruzipain, the major cysteinyl proteinase of Trypanosoma cruzi, is expressed by all developmental forms and strains of the parasite and stimulates potent humoral and cellular immune responses during infection in both humans and mice. This information suggested that cruzipain could be used to develop an effective T. cruzi vaccine. To study whether cruzipain-specific T cells could inhibit T. cruzi intracellular replication, we generated cruzipain-reactive CD4 ؉ Th1 cell lines. These T cells produced large amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 64 publications
(44 reference statements)
3
63
0
2
Order By: Relevance
“…Previous studies have shown that formulations containing distinct recombinant proteins could elicit protective immunity in BALB/c or C57BL/6 mice against a lethal challenge with T. cruzi (16,20,23,32,34). Depletions of CD4 ϩ or CD8 ϩ T cells before challenge were not performed in animals vaccinated with cruzipain or TC52 (20,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that formulations containing distinct recombinant proteins could elicit protective immunity in BALB/c or C57BL/6 mice against a lethal challenge with T. cruzi (16,20,23,32,34). Depletions of CD4 ϩ or CD8 ϩ T cells before challenge were not performed in animals vaccinated with cruzipain or TC52 (20,23).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have been published over the past 10 years demonstrating that recombinant proteins or plasmid DNA can elicit protective immunity against experimental Trypanosoma cruzi infection (2,3,4,5,7,8,12,16,20,21,23,24,28,31,32,33,34; reviewed in references 17 and 22). Vaccinated mice develop a strong cellular immune response mediated by CD4 ϩ Th1 and CD8 ϩ Tc1, thus surviving otherwise lethal acute infection.…”
mentioning
confidence: 99%
“…As is the case with many infectious disease immunization strategies, the approach to T. cruzi immunization has been focused primarily on the introduction of immunodominant targets that would initiate a strong secondary response upon primary infection with parasite (6,10,19,20,41,52,67,68,70). The novel strategy presented here was to induce an immune response to a parasite-derived immune evasion factor, in this case a B-cell mitogen.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports demonstrated the capacity of complement regulatory protein, paraflagellar rod protein, and trans-sialidases (TS), all expressed as surface antigens in T. cruzi, to elicit antiparasite immune responses capable of enhancing the survival of infected mice (9,29,31,37,38). We have shown the protective efficacy of the TS family members, namely, amastigote surface proteins ASP-1 and ASP-2 and trypomastigote surface antigen TSA-1, as DNA vaccines.…”
mentioning
confidence: 99%